Surface water quality status and prediction during movement control operation order under COVID-19 pandemic: Case studies in Malaysia - Najah A.; Teo F.Y.; Chow M.F.; Huang Y.F.; Latif S.D.; Abdullah S.; Ismail M.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
Agricultural robots; Ammonia; Forecasting; Lakes; Learning algorithms; Machine learning; Motion estimation; Multilayer neural networks; Rivers; Sensitivity analysis; Water quality; Agricultural activities; Health condition; Movement control; Multi layer perceptron; Reconnaissance surveys; Three parameters; Water quality indexes; World Health Organization; Quality control; COVID-19; lake water; river water; spatiotemporal analysis; surface water; water quality; World Health Organization; Malaysia; Penang; Putrajaya; Putrajaya Lake; West Malaysia